Discovery of Hepatitis C Virus NS3 Helicase Inhibitors by a Multiplexed, High‐Throughput Helicase Activity Assay Based on Graphene Oxide1. Issue 8 (25th January 2013) - Jang, Hongje; Ryoo, Soo‐Ryoon; Kim, Young‐Kwan; Yoon, Soojin; Kim, Henna; Han, Sang Woo; Choi, Byong‐Seok; Kim, Dong‐Eun; Min, Dal‐Hee
<x xml:space="preserve">Abstract</x> A GO‐to solution: A simple graphene oxide (GO)‐based assay to screen for selective inhibitors of a hepatitis C virus (HCV) helicase along with inhibitors of a severe acute respiratory syndrome coronavirus (SARS CoV) helicase was tested (see scheme). A single screen found five inhibitors highly selective for the HCV helicase orthologous to the SARS CoV helicase. Some of these hits were validated using the same GO‐based assay.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>